State-sponsored trade unions after democratic transitions. Issue 7 (2nd October 2020) - Fedorowycz, Daniel; A. C. Gatto, Malu; Maydom, Barry
ABSTRACT: New democracies inherit a variety of institutions from prior authoritarian regimes, including political parties, militaries and entrenched oligarchies. While these authoritarian legacies have generally been well-researched, one set of institutions has received relatively little attention: state-backed trade unions that lose official sponsorship after democratizing transitions. In most new democracies and competitive authoritarian regimes, these "legacy unions" have remained the dominant workers' organizations despite few internal reforms. Previous research on the causes and consequences of legacy union dominance has rested on case studies of post-transition countries and small-N comparisons. In this article, we offer a global perspective on the fates of legacy unions by introducing new data about the relative importance of legacy unions in post-Third Wave democracies. We show that most legacy unions survive democratic transitions and remain dominant in new democracies, although with significant regional variation. Our data and analyses suggest that these trade unions are authoritarian legacies which continue to influence labour politics in new democracies. Dominant legacy unions are associated with lower labour movement fragmentation and better-protected labour rights in new democracies.